Theoretically studying the optoelectronic properties of oligomers based on 2.7-divinyl-cabazole - Jabha, Mohamed; El Alaoui, Abdellah; Jarid, Abdellah; Mabrouk, El Houssine (Eclética Química, 2022)
This work consists of theoretically studying the electronic and optical properties of 9-(4-octyloxyphenyl)-2.7-divinyl-carbazole (PCrV) oligomers. This study has been undertaken using the density functional theory (DFT) method at the B3LYP/6-31G (d,p) level and BP86/6-31G (d,p) level of theory. To evaluate the PCrV-basis systems properties, the structural optimization without geometrical restrictions was performed on the total potential energy surface (TPES). In order to ensure good absorption of radiation, the interest was in increasing the efficiency of the organic photovoltaic cell. For this effect, the (HOMO-LUMO) gap energy of such compounds was reduced in terms of geometric and electronic structure. The BP86 functional gives good results at the energy gap level, while other parameters using the B3LYP functional give the best results.